Gestión del conocimiento y su incidencia en el desempeño laboral del gad municipal de buena fe 2023 - Contreras Cañola, Yomber Yoximar (2025)
The present research focuses on how knowledge is managed and its influence on work performance in the GAD Municipal de Buena Fe during the year 2023. The study was organized in three main areas: the evaluation of current knowledge management practices, the impact of internal communication on work performance, and the identification of the main obstacles that hinder its effective implementation. A mixed methodological approach was used, combining qualitative techniques, such as interviews with managers, and quantitative techniques, through surveys of administrative staff. The results show that, despite significant progress in the implementation of document policies and systems, there is still a critical perception among some of the staff regarding their effectiveness. With regard to internal communication, although most of them value positively the existing channels, difficulties were identified in the coordination between departments. In addition, three key limitations were found: insufficient technological infrastructure, lack of incentives for knowledge sharing and time restrictions for activities related to its management. The conclusions highlight the need to strengthen knowledge management processes, optimize communication mechanisms and promote structural and cultural transformations to overcome existing barriers. Therefore, it is recommended to strengthen document management, consolidate effective multichannel communication and improve the technological infrastructure as essential measures to enhance institutional work performance.